Corrosion engineering handbook. atmospheric and media corrosion of metals - Schweitzer, Philip A. (Corrosion Engineering Handbook, Second Edition., 2007)
Understanding corrosion is essential for selecting and maintaining equipment and structural components that will withstand environmental and process conditions effectively. Fundamentals of Metallic Corrosion: Atmospheric and Media Corrosion of Metals focuses on the mechanisms of corrosion as well as the action of various corrodents on metals and their alloys. The book is tailored to support specialists studying corrosion in metallic materials or using metallic materials. The first chapters describe different forms of metallic corrosion and the effects of atmospheric corrodents such as.